MODEL PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL KALIMANTAN TIMUR INTEGRASI NILAI BUDAYA DALAM PENDIDIKAN ABAD 21 - Achmad Ruslan Afendi (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2026)
The era of globalization, marked by advances in information technology and the flow of cross-border cultures, has brought significant impacts on changes in the values and behaviors of the younger generation. On the one hand, globalization opens opportunities for progress; on the other hand, it triggers serious challenges in the form of moral degradation, weakening character, and a crisis of local cultural identity. This condition requires strengthening character education that is not only normative but also contextual, rooted in local wisdom values as a source of shaping students’ identity. East Kalimantan, as a region rich in cultural diversity, has great potential to integrate local values into character education. This study aims to develop a character education model based on the local wisdom of East Kalimantan that is relevant to the needs of 21st-century education. The research method used is a descriptive qualitative approach, through stages of exploring local cultural values, formulating a conceptual model, and limited implementation testing in educational institutions. Data collection techniques include observation, in-depth interviews, and documentation, with data analysis using an interactive model. The results of the study indicate that a character education model based on the local wisdom of East Kalimantan can be formulated as an integrative-holistic model that combines values of religiosity, mutual cooperation, tolerance, social responsibility, and environmental awareness within the learning process. This model is implemented through curriculum integration, culture-based contextual learning, extracurricular activities, and teacher role modeling. The implications of this study show that strengthening character education based on local wisdom not only improves students’ moral quality but also reinforces cultural identity and the relevance of education to the social context of society. Therefore, this model can serve as a strategic alternative for developing educational policies and practices in the region, particularly in supporting the creation of a generation that is characterized, cultured, and adaptive in the global era